Logic-based program synthesis and transformation : 28th International Symposium, LOPSTR 2018, Frankfurt/Main, Germany, September 4-6, 2018, Revised selected papers /: 28th International Symposium, LOPSTR 2018, Frankfurt/Main, Germany, September 4-6, 2018, Revised selected papers. (2019) - Unknown
No abstract available